Determination of viscosity curves based on limited rheological measurements - Wilczyński, K. J. (Polimery, 2021)
A method of determining the viscosity curves on the basis of limited number of rheological measurements has been developed using mass flow rate (MFR) index. Several models have been applied, a universal Vinogradov-Malkin, two-parameter Ostwald-de Waele power-law, and three-parameter logarithmic Klein equation. The method has been verified using high density polyethylene (HDPE) rheological studies. It has been found that the proposed procedures can be useful in engineering practice for rapid assessment of rheological properties of the processed materials, especially new and advanced ones, (e.g., polymer blends or polymer composites), for which no rheological data were available in materials databases.